The Effect of Lateral Hurdle Hops Training on Increasing Leg Muscle Explosive Power in Volleyball Players of the Patriot Paninjauan Club, Tanjung Raya District - aksha, alan nuril; Muhammad Sazeli Rifki,; Bafirman,; Liza, (Jurnal IKEOR, 2026)
The problem in this study is the still low explosive power of the leg muscles of volleyball players at the Patriot Paninjauan Club, Tanjung Raya District. The purpose of this study was to determine the effect of lateral hurdle hops training on increasing the explosive power of the leg muscles of volleyball players at the Patriot Paninjauan Club, Tanjung Raya District. This research is a quasi-experimental study. It was conducted from July to August 2025 at the Patriot Paninjauan volleyball court in Tanjung Raya District. The population consisted of all 24 volleyball players from the Patriot Paninjauan Club in Tanjung Raya District. The sampling technique used purposive sampling, resulting in a sample size of 14 players. The instrument for data collection was the vertical jump test. The data analysis technique used statistical analysis using the mean difference test or t-test. The results of this study are: There is an effect of lateral hurdle hop training on the explosive power of the leg muscles of the Patriot Paninjauan Club volleyball players in Tanjung Raya District, with a t-test of 2.96 > t-table of 1.77, resulting in an average increase of 2.2 points in leg muscle explosive power. This means that lateral hurdle hop training is very effective in improving the explosive power of the leg muscles.